2022
DOI: 10.1155/2022/5213744
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Influencing Cerebrospinal Fluid Leaking following Pituitary Adenoma Transsphenoidal Surgery: A Meta-Analysis and Comprehensive Review

Abstract: Background. Surgical resection is the main method to treat pituitary adenoma. Cerebrospinal fluid leakage (CSF Leak) is the main complication after transsphenoidal surgery. The impact of postoperative CSF Leak can be predicted in advance, and preventive measures can be taken in time. Clinically, a variety of factors may affect the occurrence of postoperative CSF Leak. In this study, meta-analysis was used to investigate the risk factors of postoperative CSF Leak as a clinical reference. Methods. The databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…In another study, CSF leaks were associated with large tumor volume and level of tumor invasiveness [ 12 ]. One meta-analysis on post-operative CSF leak risk factors after pituitary adenoma transsphenoidal surgery showed body mass index, tumor size, revision surgery, and intraoperative CSF leak as significant factors [ 13 ]. However, none of these factors were significant in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, CSF leaks were associated with large tumor volume and level of tumor invasiveness [ 12 ]. One meta-analysis on post-operative CSF leak risk factors after pituitary adenoma transsphenoidal surgery showed body mass index, tumor size, revision surgery, and intraoperative CSF leak as significant factors [ 13 ]. However, none of these factors were significant in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, it is a multicentre dataset (30 centres in the UK and Ireland), collected via a prospective observational study in 3 phases encompassing November 2019 – July 2020 ( 22 25 ). All TSA (defined as transsphenoidal access to the sella alone) and EEA [defined as acquiring surgical access to an area beyond the sella ( 17 , 19 )] were included. The dataset is composed of baseline characteristic data (e.g., age; sex; tumour diameter), operative data (e.g., intraoperative CSF leak presence; skull base repair method) and postoperative outcomes (e.g., CSFR) ( 22 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous risk factors have been identified for CSFR, including the presence of intraoperative cerebrospinal fluid (CSF) leak; revision surgery; and high body mass index (BMI) ( 19 ). A particularly important factor is the choice of skull base repair technique used intraoperatively ( 7 , 10 , 13 , 16 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…BioMed Research International has retracted the article titled "Factors Influencing Cerebrospinal Fluid Leaking following Pituitary Adenoma Transsphenoidal Surgery: A Meta-Analysis and Comprehensive Review" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…BioMed Research International has retracted the article titled “Factors Influencing Cerebrospinal Fluid Leaking following Pituitary Adenoma Transsphenoidal Surgery: A Meta-Analysis and Comprehensive Review” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%